2021
DOI: 10.3390/genes12040604
|View full text |Cite
|
Sign up to set email alerts
|

QTL Analysis of Five Morpho-Physiological Traits in Bread Wheat Using Two Mapping Populations Derived from Common Parents

Abstract: Traits such as plant height (PH), juvenile growth habit (GH), heading date (HD), and tiller number are important for both increasing yield potential and improving crop adaptation to climate change. In the present study, these traits were investigated by using the same bi-parental population at early (F2 and F2-derived F3 families) and late (F6 and F7, recombinant inbred lines, RILs) generations to detect quantitative trait loci (QTLs) and search for candidate genes. A total of 176 and 178 lines were genotyped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 119 publications
(148 reference statements)
0
12
0
Order By: Relevance
“…Plant height plays a crucial role in biomass accumulation and grain yield and all six-multi-locus models identified QTNs associated with this well-studied trait on chromosomes 1A, 2A, 3A, 4B, 5B, 7A, and 7B, consistent with QTLs reported in previous studies [ 33 36 ]. Two of them were localized ~ 9 kb far from the main Rht-B1 gene controlling PH trait on chromosome 4B [ 37 ], in the same genomic region where a QTL for the same trait was identified by Vitale et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plant height plays a crucial role in biomass accumulation and grain yield and all six-multi-locus models identified QTNs associated with this well-studied trait on chromosomes 1A, 2A, 3A, 4B, 5B, 7A, and 7B, consistent with QTLs reported in previous studies [ 33 36 ]. Two of them were localized ~ 9 kb far from the main Rht-B1 gene controlling PH trait on chromosome 4B [ 37 ], in the same genomic region where a QTL for the same trait was identified by Vitale et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This region contains Rht-B1 gene regulating plant height. Previously, QTLs associated with PH, SL, GY and GNS have been reported in this region [ 15 , 17 , 24 , 29 , 33 ]. In the interval of 112–342.7 Mb on 4D, PH QTLs ( Qph-Irr.tab-4D and Qph-Wd.tab-4D ) were mapped with R 2 value ranging from 9.04 to 18.6%.…”
Section: Discussionmentioning
confidence: 99%
“…To develop drought tolerant varieties it is essential to understand the genetic basis of these complex traits [ 4 ], thus identification of quantitative trait loci (QTL) and genes for important agronomical traits such as grain yield and its components is a key component of crop improvement programs [ 5 ]. To date, a large number of QTLs associated with yield component traits and grain yield under water deficit condition [ 1 , 2 , 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and normal condition [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] have been identified on all 21 wheat chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Forty-six individuals, derived from the tails of a bi-parental recombinant inbred line population (RIL F6:7 ), previously studied for five high-correlated morpho-physiological traits (i.e., plant height, juvenile growth habit, total tiller number, fertile tiller number and heading date) ( Vitale et al, 2021 ), were analyzed. The population of 176 RILs was developed from a cross between Lankaodali and Rebelde bread wheat cultivars, using the single seed descent method by advancing random F2 plants to the F6:F7 generation ( Vitale et al, 2021 ). The two parental accessions were characterized by contrasting quantitative and qualitative agronomic traits ( Botticella et al, 2018 ; Vitale et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Martinez et al (2020) combined WES with BSA to map ethylmethanesulfonate mutations and identified a novel allele linked to the wheat ERA8 ABA-hypersensitive germination phenotype. Within this motivating context, this study aimed to determine the efficacy of WES for identifying useful alleles within a recombinant inbred line (RIL) population of 46 individuals plus the two parents selected from a previous work in which the entire RIL population was used to identify genomic regions associated with target traits: plant height (PH), juvenile growth habit (GH), heading date (HD), fertile tiller number (FTN) and total tiller number (TTN) ( Vitale et al, 2021 ). We identified many single nucleotide polymorphisms (SNPs) that were classified based on their genomic location and putative biological effect.…”
Section: Introductionmentioning
confidence: 99%